Synthesizing Spirituality and Business: Exploring the Economic Dimensions of Sufism Orders in Indonesia - Munandar, Siswoyo Aris (Jurnal Dakwah, 2022)
AbstractSo far, the general view of the tarekat teaches to stay away from the world, only to carry out worship. Moreover, his doctrines live for the hereafter and distance themselves from the world of asceticism. In addition, Sufis are often imagined as someone who looks simple, even tends to be what he is. that the Sufis are a collection of poor, poor and desperate people. This opinion is not completely wrong and not completely correct. Therefore, in this study the author wants to show that the tarekat are also in business. This research is a descriptive-qualitative research by prioritizing primary data sourced from field studies; and using secondary data as a supporting source. The use of this descriptive-qualitative method aims to describe the construction of business, which is influenced by both religion and culture, in the economic activities carried out by entrepreneurs following the tarekat in Indonesia. The results of this study show that the Idrisiyyah Tarekat is not only engaged in education and da'wah, but is also engaged in the economic field, not less than 40 business units developed by Pesantren Idrisiyyah. The Tarekat Shiddiqiyyah through its members also carries out many economic activities that can help the lives of the surrounding community. Some of the business units formed include star hotels, bottled mineral water production, kretek cigarette business partners, cigarette companies, health clinics, honey production, handicrafts and restaurants.  AbstrakSelama ini Pandangan umum terhadap tarekat itu mengajarkan untuk jauh dari dunia, hanya sebatas menjalankan ibadah. Apalagi doktrin-doktinnya hidup untuk akherat dan menjauhkan diri dari dunia zuhud. Selain itu Sufi kerap dibayangkan sebagai seorang yang berpenampilan sederhana, bahkan cenderung apa adanya. bahwa sufi itu kumpulan orang-orang fakir, miskin dan putus asa. Pendapat ini tidak sepenuhnya salah dan tidak sepenuhnya benar. Oleh karena dalam penelitian ini penulis ingin menunjukan bawah kaum tarekat juga berbisnis. Penelitian ini merupakan penelitian deskriptif-kualitatif dengan mengendepankan data primer yang bersumber dari kajian lapangan; dan menggunakan data sekunder sebagai sumber pendukung. Pemakaian metode deskriptif-kualitatif ini bertujuan untuk menggambarkan konstruksi bisnis, yang dipengaruhi baik oleh agama maupun budaya, dalam aktivitas ekonomi yang dijalakan oleh pengusaha pengikut tarekat-tarekat di Indonesia. Hasil dari penelitian ini bahwa Tarekat Idrisiyyah tidak hanya bergerak dalam bidang pendidikan dan dakwah, tapi juga bergerak dalam bidang ekonomi, tidak kurang dari 40 unit usaha yang dikembangkan oleh Pesantren Idrisiyyah. Tarekat Shiddiqiyyah lewat anggota-anggotanya juga banyak melakukan aktivitas ekonomi yang dapat membantu kehidupan masyarakat sekitarnya. Beberapa unit usaha yang dibentuk diantaranya, hotel bintang, produksi air mineral kemasan, mitra usaha sigaret kretek, perusahaan rokok, klinik kesehatan, produksi madu, kerajinan tangan dan rumah makan.